(untitled) (Jurnal Simki Economic, 2024)
This research is to determine the level of financial health of BUMN based on BUMN ministerial decree Number: KEP-100/MBU/2002 at PT. X period 2017-2022. This research uses a quantitative descriptive method with eight indicators, namely: ROE, ROE, Current Ratio, Cash Ratio, Collection Periods, Inventory Turnover, Total Assets Turnover, and Total Own Capital to Total Assets. From the results of research that has been carried out, in 2027 and 2018 they received scores of 53 and 50 so they were included in the "Unhealthy" category with the predicate "BBB". In 2019 it decreased to 44, falling into the "Unhealthy" category with the predicate "BB". In 2020 and 2021 the score rose to 49 and 51, falling into the same category, namely "Unhealthy" but with the predicate "BB" for 2020 and "BBB" for 2021. In 2022, the score dropped drastically to 44, so it fell into the category “Unhealthy” with the predicate “BB”. It can be concluded that during the 2017 – 2022 period, based on an assessment of the financial aspects of PT. X is in a “Unhealthy” condition.